Floquet Harper-Hofstadter Butterflies and non-Hermitian phase transition in quasicrystals - Kremer, Mark; Weidemann, Sebastian; Longhi, Stefano; Wimmer, Martin; Peschel, Ulf; Szameit, Alexander (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
The non-Hermitian Aubry-André-Harper model exhibits a non-Hermitian phase transition that coincides with a localization transition. We provide a high-resolution measurement of the Butterfly spectrum and propose experiments to measure those transitions, using a photonic lattice.
CRIS-Team Scopus Importer:2023-04-20